PENGEMBANGAN MEDIA E-LEARNING BERBASIS APLIKASI ANDROID PADA MATERI PENJUMLAHAN DAN PENGURANGAN ALJABAR KELAS VII - Ilyas Arddy Sukma; Dede Suratman; Dian Ahmad (Universitas Tanjungpura, 2020)
Abstract This study aimed to find out the validity of e-learning media based on android application on the addition and subtraction of algebraic material and students responses toward it. The approach of this study was Research and Development and used ADDIE model. The study consists of 5 stages namely analyze, design, develop, implement and evaluate. The sample of the research was class VII students of SMP Mandiri Pontianak. The instrument used in form of a sheet of validity of e-learning media based on android application and questionnaire. The expert validation value of e-learning media based on android application was 3.4 and categorized as valid. Furthermore, the expert validation value of e-learning media based on android application was 3.44 and categorized as valid. The students gave positive respond toward e-learning media based on android application in percentage amount of 71.62%. Thus it, can be summarized that e-learning media based on android application on the addition and subtraction of algebraic material is valid so it is worth to be used as a learning medium and students responses was categorized as positive in cognitive, affective, and psychomotor aspect. Keywords: addition and subtraction of algebraic, android application, e-learning media, students’ responses,